PERENCANAAN STRUKTUR ATAS GEDUNG DEKANAT UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT KAMPUS IV PAYAKUMBUH - Muhammad Iqbal Yuhanda; Deddy Kurniawan; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This building is one of the dean's buildings of the University of Muhammadiyah West Sumatra campus IV located in the Payakumbuh area which aims to improve educational facilities and infrastructure. To realize a safe development, careful planning is needed, so that when the building is completed and ready for the building it is safe and comfortable to use. The results obtained that the material used is steel fy = 420 MPa and concrete quality fc' = 24.9 MPa. For the reinforcement of floor slabs, reinforcement is used for the direction of x = 10 – 150, while the direction of y = 10 – 150. The planning of the columns for the 1st and 2nd floors uses steel quality fy = 420 MPa and concrete quality fc' = 24.9 MPa with K1 size 45cm x 45cm, and the 3rd floor column uses steel quality fy = 420 MPa and concrete quality fc' = 20.75 MPa with K2 size 30cm x 30cm. While planning for beam 1 with a size of 35cm x 55cm using steel quality fy = 420 MPa and concrete quality fc' = 24.9 MPa, beam 2 with a size of 25cm x 45cm using steel quality fy = 420 MPa and concrete quality fc' = 20.75 MPa, and a beam with a size of 25cm x 40cm using steel quality fy = 420 MPa and concrete quality fc' = 20.75 MPa. Keywords: Building Structure, Education, Reinforcement.